Early nasal microbiota and subsequent respiratory tract infections in infants with cystic fibrosis - Ruth Steinberg; Nadja Mostacci; Elisabeth Kieninger; Bettina Frauchiger; Carmen Casaulta; Jakob Usemann; Alexander Moeller; Daniel Trachsel; Isabelle Rochat; Sylvain Blanchon; Dominik Mueller-Suter; Barbara Kern; et al. (Communications Medicine)
Abstract Background Respiratory tract infections (RTIs) drive lung function decline in children with cystic fibrosis (CF). While the respiratory microbiota is clearly associated with RTI pathogenesis in infants without CF, data on infants with CF is scarce. We compared nasal microbiota development between infants with CF and controls and assessed associations between early-life nasal microbiota, RTIs, and antibiotic treatment in infants with CF. Methods We included 50 infants with CF and 30 controls from two prospective birth cohorts followed throughout the first year of life. We collected 1511 biweekly nasal swabs and analyzed the microbiota after amplifying the V3–V4 region of the 16S rRNA gene. We conducted structured weekly interviews to assess respiratory symptoms and antibiotic treatment. We calculated generalized additive mixed models and permutational analysis of variance. Results Here, we show that the nasal microbiota is already altered before the first RTI or antibiotic treatment in infants with CF. Microbiota diversity differs between infants with CF and controls following RTIs and/or antibiotic treatment. CF infants with lower α-diversity have a higher number of subsequent RTIs. Conclusions Early nasal microbiota alterations may reflect predisposition or predispose to RTIs in infants with CF, and further change after RTIs and antibiotic treatment. This highlights the potential of targeting the nasal microbiota in CF-related RTI management, while also questioning current practices in the era of novel modulator therapies.